Kegiatan Edukasi Karakteristik Pengguna Narkoba di Lingkungan Pondok Pesantren Manaratul Islam Jakarta Selatan Sebagai Upaya Mewujudkan Generasi Bebas Narkoba - Fransiskus Samuel Renaldi; Khrisna Pangeran (JURNAL PENGABDIAN KADER BANGSA, 2026)
This study explores the role of Manaratul Islam Islamic Boarding School in South Jakarta in preventing drug abuse among its students. The increasing prevalence of drug abuse among adolescents has raised concerns about their well-being and future. Educational institutions, including Islamic boarding schools, play a crucial role in addressing this issue. The purpose of this study was to investigate how Islamic boarding schools implement drug prevention programs and their impact on students' knowledge, attitudes, and behaviors regarding drugs. Usinga case study design with a mixed methods approach, data was collected through semi- structured interviews and Focus Group Discussions(FGDs) with students, program facilitators, and community leaders. Findings indicate that the intervention resulted in a significant increase instudents' understanding of drug abuse, confirming the effectiveness of the combination of education, peer support systems, and community engagement. This study highlights the importance of religious and educational institutions in shaping a drug- free generation and recommendsthat similar programs be implemented across other Islamic boarding schools to increase awareness and prevent drug abuse more widely.